Evolution of the ionizing background at high redshifts - ESPEY, BRIAN RUSSELL (My University, 1997)
The decrease in number density of Lyman alpha clouds near the background quasar is an observational result that is often called the `proximity' or `inverse' effect. It is thought that, for nearby clouds, the flux of the quasar dominates the background radiation field, increasing the ionization state of the clouds and reducing the (observed) Hi column density. In this paper we analyse a sample of 11 quasars from the literature for which accurate column density estimates of the Lyman alpha lines exist. We confirm, to a significance level of more than 3sigma, that the proximity effect exists. If it is related to the background flux then the intensity and evolution of the background have been constrained . Using a maximum-likelihood method, we determine the strength of the extragalactic ionizing background for 2.0<z<4.5, taking account of possible systematic errors in our determination and estimating the effect of biases inherent in the data. If the background is constant we find that it has an intensity of 100^+50_-30 J_23, where J_23 is defined as 10^-23 erg s^-1 cm^-2 sr^-1 Hz^-1. T here is no significant evidence for a change in this value with redshift.
PUBLISHED
Keywords: Physics